SIMULATION OF THE VACCINATION OF COVID-19 MODEL IN DKI JAKARTA - Atlant Tungga, Rifaldy
In this study, the information of how long the Covid-19 vaccination program should be conducted was provided as one of the mitigation efforts to Covid-19 outbreak in DKI Jakarta. The period of vaccination program would be implemented according to the number of immune populations that resulted from vaccination or recovery following infection. In practice, an SIR (Susceptible, Infected, Recovered) model that encompassed vaccination and re-infection factors was created. In this article, the unrecorded number of daily infections was estimated in order to obtain aptly accurate results. It became a concern since the government had not entirely recorded the latest daily infection data. The estimation was conducted based on the positivity rate obtained from the government’s data. The solution of each compartment was determined based on the Richard curves function. According to the results, the number of latest daily infections of I(t) obtained from the model indicates the same trend as that of daily infections data. The correlation between positivity rate and daily active cases as well as the correlation between ?(t) and daily active cases give a good correlation coefficient number. According to the numerical simulation, DKI Jakarta has achieved the herd-immunity level since october 2021.